Chromoendoscopy in combination with random biopsies does not improve detection of gastric cancer foci in CDH1 mutation positive patients - Hüneburg, Robert; Marwitz, Tim; van Heteren, Peer; Weismüller, Tobias J.; Trebicka, Jonel; Adam, Ronja; Aretz, Stefan; Perez Bouza, Alberto; Pantelis, Dimitrios; Kalff, Jörg C.; Nattermann, Jacob; Strassburg, Cristian P. (Endoscopy International Open, 2016)
Background and study aims: Hereditary diffuse gastric cancer (HGGC), an autosomal dominant tumor-syndrome, accounts for 1 % to 3 % of gastric cancers worldwide. Presumably 30 % to 40 % of all patients fulfilling the clinical guidelines for HDGC are carriers of a pathogenic mutation in the CDH1 gene. Patients often show multiple foci of signet ring cell carcinoma at early age and are advised to undergo prophylactic total gastrectomy (PTG). Our aim was to improve the endoscopic detection of HDGC by using an enhanced endoscopic protocol. Patient and methods: Patients with a proven CDH1 germline mutation identified in our institute were prospectively included. Patients were advised to undergo PTG and offered a baseline endoscopic examination prior surgery. Examination was performed by using high-resolution white-light endoscopy and pan-gastric chromoendoscopy with indigo carmine as dye combined with targeted and multiple random biopsies assessed by an expert histopathologist. Postoperative histopathology was compared with results from endoscopic biopsies. Results: Between September 2012 and November 2014 8 patients with a proven CDH1 germline mutation were included. We conducted 44 targeted (6.3/patient) and 225 random (32.1/patient) biopsies in 7 patients. We detected 1 gastric cancer by random biopsy (14 %). All other examinations showed no signs of cancer. Histopathology of gastrectomy specimen revealed multiple foci of gastric carcinoma in 6 patients (86 %) with a total number of 27 cancer foci. Conclusions: Examination with targeted and random biopsies combined with chromoendoscopy is not able to detect small foci of gastric cancer in CDH1 mutation carriers. Therefore PTG is advocated in these patients.